2015
DOI: 10.1016/j.profoo.2015.01.043
|View full text |Cite
|
Sign up to set email alerts
|

Potency of Combination of Palm Kernel Meal and Katuk Leaf Powder to Improve the Production Performance of Peranakan Etawa (PE) Goat: Toward a Strategy for Quality Control of Meat Using “CGE” Concept

Abstract: This research was aimed to study the potency of suplementation of a combination of palm kernel meal and katuk leaf powder (Sauropus androgynus L. Merr) to the production performance in PE goat. The final target of this study is to develop a strategy for quality control of meat using a "clean, green, and ethical" (CGE) concept of technology. This study were used 20 male PE goat at aged of + 1.5 years and weight of 15-20 kg. The result showed that the suplementation of BISKAT was induced a higher level of testos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…A similar report by Rachmawati et al (2014) showed significantly different testosterone concentrations in Kejobong, Bligon, and Etawah grade buck at 12.00±6.56 ng/mL, 9.23±4.73 ng/mL, and 6.82±4.18 ng/mL, respectively. Meanwhile, Ferasyi et al (2015) determined a testosterone concentration of 13.20±3.96 ng/mL in Etawah grade bucks. Testosterone concentrations of Kacang goats were determined at 10.2±5.42 ng/mL (Armansyah et al 2018), and 7.25±1.45 ng/mL (Gholib et al 2016).…”
Section: The Concentration Of Testosteronementioning
confidence: 99%
“…A similar report by Rachmawati et al (2014) showed significantly different testosterone concentrations in Kejobong, Bligon, and Etawah grade buck at 12.00±6.56 ng/mL, 9.23±4.73 ng/mL, and 6.82±4.18 ng/mL, respectively. Meanwhile, Ferasyi et al (2015) determined a testosterone concentration of 13.20±3.96 ng/mL in Etawah grade bucks. Testosterone concentrations of Kacang goats were determined at 10.2±5.42 ng/mL (Armansyah et al 2018), and 7.25±1.45 ng/mL (Gholib et al 2016).…”
Section: The Concentration Of Testosteronementioning
confidence: 99%
“…An important issue here is the concept of 'fit but not fat'males that are overweight and do not get exercise can perform poorly, even when they have maximum testicular mass. In Indonesia, the options for male goats include katuk leaf powder and palm kernel meal (Ferasyi et al, 2015).…”
Section: Feed Males For Fertilitymentioning
confidence: 99%
“…There are few studies on the chemical composition and biological features of leaves [ 8 , 9 ], and to our knowledge, there are few data on the effects of S. androgynus leaves on ruminant animal models [ 10 ]. The objectives of this study were to investigate the phenolic profile of S. androgynus leaf extracts using high-performance liquid chromatography with diode array detection (HPLC-DAD) and to assess their biological potential for ruminant health.…”
Section: Introductionmentioning
confidence: 99%